2012
DOI: 10.1111/j.1530-0277.2012.01759.x
|View full text |Cite
|
Sign up to set email alerts
|

A Mouse Model for Adolescent Alcohol Abuse: Stunted Growth and Effects in Brain

Abstract: Ethanol treatment significantly reduced the mass of the cerebral cortex in peri-adolescent (-3.1%), but not adult, treated mice. By contrast, ethanol significantly reduced the length of the corpus callosum in adult (-5.4%), but not peri-adolescent, treated mice. Future studies at the histological level may yield additional details concerning ethanol and the peri-adolescent brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 83 publications
2
7
0
Order By: Relevance
“…Over the course of the entire experiment, adolescent body weight increased steadily from an average of 14 g on PND 28 to an average of 21 g on PND 42. The rate of body weight gain did not change following tianeptine pretreatment and is consistent with the published literature for mouse body weight at these ages (Huang et al., ).…”
Section: Resultssupporting
confidence: 91%
“…Over the course of the entire experiment, adolescent body weight increased steadily from an average of 14 g on PND 28 to an average of 21 g on PND 42. The rate of body weight gain did not change following tianeptine pretreatment and is consistent with the published literature for mouse body weight at these ages (Huang et al., ).…”
Section: Resultssupporting
confidence: 91%
“…65 It is widely acknowledged that the human adolescent brain is not fully mature, 66,67 and there is evidence from animal studies that exposure to alcohol during adolescence can affect subsequent brain/behavior development. 68,69 Voluntary consumption of ethanol (at a concentration of 8.5 g/L that led to a dose of 1.0-1.5 g/kg), caffeine (at a concentration of 170 mg/L that led to a dose of 20-30 mg/kg), or an ethanol-caffeine combination during late adolescence in male and female rats had effects on the subsequent adult behavior that were dependent on the sex of the rats. 70 Males showed more ambulation after exposure to the alcohol-caffeine mixture, while females exposed to the mixture showed the opposite effects, that is, suppressed ambulation.…”
Section: Caffeine-ethanol Interactions: Effects On Locomotionmentioning
confidence: 99%
“…Female binge drinkers (BD) had thicker left frontal cortices whereas male binge drinkers (BD) had thinner left frontal cortices compared to gender matched controls [107,102]. The existing literature also indicates that females often consume more ethanol and/or respond differently to ethanol than their male counterparts [103], although only small differences in mass measurements of the brain, the cerebellum, and the corpus callosum were seen either as a result of age (from P70 to 225), gender, or ethanol treatment.…”
Section: The Physiological Effects Of Alcohol Abusementioning
confidence: 93%
“…Results from a recent longitudinal brain imaging study of male P rats (from P88 to 578) have revealed that free-choice ethanol consumption attenuated the growth and expansion of brain structures, including the corpus callosum and hippocampus [103]. In the case of the hippocampus, these changes may relate to the inhibition of neurogenesis established to take place in this structure [102].…”
Section: The Physiological Effects Of Alcohol Abusementioning
confidence: 99%